2004
DOI: 10.1111/j.1468-2982.2004.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Headaches in People with Multiple Sclerosis

Abstract: The aim was to investigate the lifetime prevalence of headache and primary headache (diagnoses according to International Headache Society criteria) in multiple sclerosis (MS). The relationships between headache and clinical features of MS and MS therapy were also investigated. We studied 137 patients with clinically definite MS; 88 reported headache, 21 of whom developed headache after the initiation of interferon. The prevalence of all headaches in the remaining 116 patients was 57.7%. Migraine was found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
67
4
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 25 publications
13
67
4
8
Order By: Relevance
“…D' Amico, et al reported an overall headache prevalence of 57.7% among MS patients which included tension-type headache (31.9%), migraine (25.0%), unclassified headache (8.6%) and cluster headache (0.8%) [11]. In the present study, the prevalence of headache was 68%, which was higher than average prevalence figures reported in other studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…D' Amico, et al reported an overall headache prevalence of 57.7% among MS patients which included tension-type headache (31.9%), migraine (25.0%), unclassified headache (8.6%) and cluster headache (0.8%) [11]. In the present study, the prevalence of headache was 68%, which was higher than average prevalence figures reported in other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…EDSS scores were not significantly correlated with gender (p>0.05). Previous studies reported a mean EDSS score of 2.5-3.4 in headache-positive MS patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, several studies have shown migraines to be more common in patients with relapsing-remitting MS, and tension-type headaches to occur more frequently in the secondary progressive form. 2 However, the implications of tension-type headaches in MS are questionable. Current epidemiological studies have not provided convincing evidence that tension-type headaches are more frequent in MS patients compared with the general population, although large-scale investigations of this headache subtype are lacking.…”
Section: Impact On Daily Functionmentioning
confidence: 99%
“…However, several other studies have shown a highly variable trend. [2][3][4][5][6][7] We did not collect data regarding current medications, such as beta-interferon therapy or specific headache management drugs, which may influence the course of headache presentation. In order to reduce questionnaire length and encourage participation, headache subtype and stage of MS were not included in the survey.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation